A Careful Hunger : Poems - Young, Judith, 1940- (Book collections on Project MUSE., 2019)
"Inspired by a class she took at the University of Kentucky with James Baker Hall and her volunteer work with UK's Women Writers Conference, Judy Young began writing poetry in the late 1970s. That soon translated into a MFA in creative writing from Warren Wilson College. In the more than 25 years that followed, Young wrote regularly, meeting every month with a group of women writers and artists in central Kentucky. Over the years, Young established provisional collections of her best work, but always refrained from seeking publication, anxious about the prospect of sharing often deeply personal poems with an audience. Despite her reservations, her renown as a poet grew within the local writing community. Judy Young died in January of 2015, but her legacy lives on in her children and considerable body of work. In A Careful Hunger, Judy Young's (1940-2015) personal poems are presented to the public for the first time. The collection is based on the final version of the work that Young drafted before her death. Several early poems have been restored and partially edited by her son to more fully convey the scope of her private literary career. It traces the path of a woman finding her poetic voice in middle age: returning to an often painful childhood; closely observing the natural world, especially the populations of birds moving through the space between her back porch and the lake below; and meditating on the nature of creativity. With a submerged narrative behind the poems and several calls to nature through repeated motifs, this collection of poems shares Young's seminal early emotions and experiences"--